Peaks and primordial black holes: the effect of non-Gaussianity. Issue 5 (1st May 2022) - Young, Sam
Abstract: In light of recent developments in the field, we re-evaluate the effect of local-type non-Gaussianity on the primordial black hole (PBH) abundance (and consequently, upon constraints on the primordial power spectrum arising from PBHs). We apply peaks theory to the full, non-linear compaction, finding that, whilst the effect of non-Gaussianity is qualitatively similar to previous findings, the effect is much less significant. It is found the non-Gaussianity parameters f NL local and g NL local typically need to be approximately 1 or 2 orders of magntiude larger respectively to have a similar to that previously found. The effect will be to weaken the dependance of PBH constraints on the primordial power spectrum on the non-Gaussianity parameters, as well as to dramatically weaken constraints on the non-Gaussianity parameters (and/or PBH abundance) arising from the non-observation of dark matter isocurvature modes. We also consider the correlation between the curvature perturbation ζ and the compaction C, finding that, whilst PBHs may form at rare peaks in C these do not necessarily correspond to rare peaks in ζ — casting some doubt on many of the existing calculations of the PBH abundance.